Status resistensi vektor Aedes aegypti terhadap malation dan enzim esterase non spesifik di kecamatan Tembalang - Irneta Bela Novita; Martini Martini; Retno Hestiningsih; Sri Yuliawati; Nissa Kusariana; Mochammad Hadi (Faculty of Medicine, Universitas Islam Indonesia, 2019)
Background: Controlling of dengue vectors around dengue haemorrhagic fever cases is often conducted by using insecticides, including a malathion insecticide in the city of Semarang. A research on susceptibility status of Ae. aegypti to insecticides, used for fogging and based on a high number of hemorrhagic fever cases in Tembalang district, Semarang city, needs to be observed.Objective: This study aimed to determine resistance status of Ae. aegypti mosquitoes based on bioassay and biochemical tests of esterase non-specific enzyme activity in the Tembalang District. Methods: This study used a cross sectional design, it was conducted in June-September 2018 in a population of Aedes sp. from Tembalang District, Semarang City. Samples of F2 generations of female Ae. aegypti were obtained by ovitraps in the Tembalang District consisting of 12 urban villages, and their resistance status were tested by impregnated paper bioassay with malathion at a diagnostic dose of 0.8%. Esterase enzyme activity in the Ae. aegypti mosquito body of this population was tested biochemically to prove an increase in a non-specific esterase enzyme on the a-naphthyl acetate substrate.Results: The bioassay results showed that mortality rates of Ae. aegypti at the 12 villages in Tembalang district after 24 hourtest by impregnated paper indicated a range of 0-62%. Mechanism of resistance indicating an increase of non-specific enzyme esterase activity on a-naphthyl acetate at Rowosari, Kedungmundu, Sambiroto, and Meteseh could not be seen, It began to be seen in a low percentage (15%) at Sendang Mulyo, Tandang, Sendangguwo and Bubusan, and in a moderate percentage (45-75%) in Tembalang, Jangli and Mangunharjo. The mechanism of high esterase enzyme activity could be seen in the Ae. aegypti population at Kramas with AV=0,700-0,900 by a percentage of 20%, and AV=0,900 by a percentage of 80%.Conclusion: This study provided information about some Ae. aegypti mosquitoes from Tembalang District that showed resistance to the malathion insecticide with an elevation of non-specific esterase enzyme activity ona-naphthyl acetate substrate in several villages except Kelurahan Rowosari, Kedungmundu, Sambiroto, and Meteseh.